A facile method for high-performance multicolor upconversion microrods for biological encoding. (21st October 2015) - Su, Lin; Gong, Xiaoqun; Wang, Sheng; Li, Xue; Zhang, Ying; Dou, Yan; Yang, Wentao; Wang, Hanjie; Chang, Jin
Abstract: In this paper, we demonstrate a facile method for preparing high-performance multicolor upconversion (UC) microrods for biological encoding. Multicolor UC microrods were prepared through a one-step facile hydrothermal method. The as-prepared UC microrods were uniform in shape and size (about 2 μ m in length). For bioconjugation, the UC microrods were functionalized by coating with an amino-terminated silica shell. In order to magnify the bioactive sites, poly (acrylic acid) was introduced to the surface of UC microrods. The optical micrographs displayed that the carboxylated UC microrods were bright enough for observation of single crystals by a conventional microscope. They also exhibited excellent fluorescence stability against time expansion and pH change. Furthermore, a conventional optical microscope can readout the results of a sandwich immunoassay that was conducted by the UC microrods. All the results indicated that the UC microrods exhibited great potential to be new encoding particles for biological molecules.